2007
DOI: 10.1111/j.1365-2141.2007.06796.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and treatment outcome of infants with non‐Hodgkin lymphoma

Abstract: Summary Non‐Hodgkin lymphoma (NHL) is rarely observed during infancy and data on its incidence, characteristics and outcome are scarce. The present study aimed to assess the prevalence, clinical presentation and treatment results of all infants who were diagnosed with NHL between October 1986 and December 2002 among 2084 patients treated according to the NHL‐BFM (Berlin‐Frankfurt‐Münster) multicentre trials 86, 90 and 95. We identified 20 (1%) infants with NHL including five with T‐cell lymphoblastic lymphoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 26 publications
3
16
0
1
Order By: Relevance
“…[13,14] Mann et al reported three patients with late relapses at 1.6, 3, and 4 years, and only two survived. [15] We report a majority of local relapses, and only a few BM relapses, as described in other studies: EORTC 58881, BFM 90-95, LSA2L2, and POG 8704 trials. [14,16] The rate of CNS relapses described in our study is low (only three patients), as reported in the previous EORTC 58881 protocol without CNS prophylactic irradiation.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…[13,14] Mann et al reported three patients with late relapses at 1.6, 3, and 4 years, and only two survived. [15] We report a majority of local relapses, and only a few BM relapses, as described in other studies: EORTC 58881, BFM 90-95, LSA2L2, and POG 8704 trials. [14,16] The rate of CNS relapses described in our study is low (only three patients), as reported in the previous EORTC 58881 protocol without CNS prophylactic irradiation.…”
Section: Discussionsupporting
confidence: 77%
“…It will allow early adjustment of front‐line treatment. Risk factors have been identified for ALL, but the situation is not as clear for lymphomas . Baleydier et al.…”
Section: Discussionmentioning
confidence: 99%
“…The median age at diagnosis for pediatric patients is approximately 10.2-11.0 years, [7][8][9] and systemic ALCL rarely occurs in infants. [9][10][11][12] Most patients with ALKnegative ALCL are adults (age range, 40-65 years), with a slight male predominance. 13 In the pediatric age group (fewer than 10%), ALK-negative ALCL is limited to single case reports or small numbers of patients in larger series.…”
Section: Discussionmentioning
confidence: 99%
“…20 The precise incidence of NHL in children is not known and the development of NHL in the early infantile period is rare. 21 It is possible that our patient developed NHL at 2 months of age owing to having the germline mutation in the proto-oncogene BRAF.…”
Section: Discussionmentioning
confidence: 98%